A comparative investigation on in-situ and laboratory standard test of the potential induced degradation of crystalline silicon photovoltaic modules. (November 2018) - Islam, M.A.; Hasanuzzaman, M.; Rahim, Nasrudin Abd
Abstract: Potential induced degradation (PID) is one of the genuinely critical concerns of a sustainable power generation from a PV system. Generally, the PID behavior of a PV module is tested in the laboratory according to the IEC standard before installation into a plant. On the other hand, an electroluminescence imaging is a reliable technique to identify the different types of PV cell defects which cause the degradation of the PV modules. The aim of this research is to investigate the PID behavior of similar PV modules in both the real on-site test and the laboratory standard test conditions. This will facilitate the outcome of the tangible indoor PID test results with more ease and reliability. It has been observed from the EL images of the on-site degraded PV module that a performance degradation happens due to different types of PV cell defects, such as, localized shunting, cracks, front contact grid interruptions, etc. The maximum power versus EL mean intensity shows a linear relationship which predicts the quantitative performance analysis of a PV module from an EL imaging process. The PID of a PV module has been found in a negative voltage stress condition in both the on-site and the laboratory tests. The shunt resistance gradually decreases as a consequence of the negative voltage stress only. The on-site degradation levels of the P max, V oc, I sc, and FF are 46.5, 7.15, 30.4, and 17.35% respectively after a duration of nearly 11 years of a negative voltage stress generated from a 240 V string size. In a laboratory PID test, the P max, V oc, I sc, and FF are degraded due to a negative voltage stress with a value of 6.83%, 1.9%, 1.5%, and 3.5% respectively. Highlights: EL image mean intensity versus P max curve of PV module shows linear relationship. Shunt resistance of PV module decreases significantly under negative voltage stress only. Shunt resistance decreases exponentially with increase aging period. Leakage current resistance properties decrease as a consequence of PID stressing.